KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA BANGGAI ( SUATU ANALISIS KONTRASTIF) - Tabialos, Retina; Jansen, Frieda Th.; Rambing, Rosalina R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACTThis study is an attempt to analyze, describe and contrast English and Bangai language which focuses on the interrogative sentences in relation to their form and function in both languages. The data of the English language were collected from books by Aarts (2001) Aarts and Aarts (1957), whereas the data of Banggai language were collected by interviewing and recording using a mobile phone recording, resulting in the collected audio material as the primary data. The data were then analyzed and described. To find out the forms and functions of interrogative sentences, the writer used theory of interrogative sentences based on Aarts (2001). After that, the data were contrasted by using Lado’s theory (1957). The results of this study show that these two language have differences as well as similarities. There are eight similarities and eight differences between both languages. Keywords : Interrogative Sentence, English and Banggai Language, Contrastive Analysis.